Local consequences of global uncertainty: Capacity development and LNG trade under shale gas and demand uncertainty and disruption risk - Ruud Egging; Franziska Holz (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Recent supply security concerns in Europe have revived interest into the natural gas market. Here, we investigate investment behavior and trade in an imperfect market structure under uncertainty in both supply and demand. We focus on three uncertain events: i) transit of Russian gas via Ukraine that may be disrupted from 2020 on; ii) natural gas intensity of electricity generation in OECD countries that may lead to higher or lower natural gas demand after 2025; and iii) availability of shale gas around the globe after 2030. We illustrate how timing of investments is affected by inter-temporal hedging behavior of market agents, such as when LNG capacity provides ex-ante flexibility (e.g., in Ukraine to hedge for a possible Russian supply disruption) or an expost fallback option if domestic or nearby pipeline supply sources are low (e.g., uncertain shale gas resources in China). Moreover, we find that investment in LNG capacities is more determined by demand side pull (due to higher needs in electric power generation) than by supply side push (higher shale gas supplies needing an outlet).
Keywords: C73; L71; Q34; 330; stochasticity; mixed complementarity model; natural gas